Prospect for detecting squeezed states of light created by a single atom in free space - Stobinska, Magdalena; Sondermann, Markus; Leuchs, Gerd (Optics Communications, 2010)
We discuss the possibilities of studying in detail the dynamics of spontaneous emission of a single photon by a single atom and measuring the transient degree of squeezing by means of full solid angle fluorescence detection. © 2009 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2010.nat.dphy.optik.1optik.prospe
Keywords: Resonance fluorescence; Single atom; Single photon; Squeezing